Determinants of Zakat Behavior - Asiati, Diah Isnaini; Nopriyansah, Reza (International Journal of Business, Management and Economics, 2020)
Zakat is a popular Islamic weapon in shaping the welfare of society which has moral, social, and economic values. Economically, zakat balances social life by distributing wealth from rich people to poor societies. However, the greatness that is aimed to be realized was not sufficient in encouraging people to implement zakat itself, even for its value owners which is Moslem’s community. This is why the target of obtaining zakat in each region as well as national does not always achieved. This research tries to find answers that explain why people are willing to pay zakat. The development of the idea is carried out by taking all the indicators that indicate the willingness of people to pay zakat. The number of indicators reaches 52 statements. The research was developed with a causal design based on primary data. A total of 100 people were determined by cluster sampling who were involved in filling out questionnaires related to zakat behavior. The respondents came from all sub-districts in Palembang City. The data obtained is then processed using analysis factor in order to determine the choice factors that can be used as the basis for zakat behavior. The selected factors are then processed using multiple linear regression. The results showed that there are 12 factors that can be identified as the basis for zakat behavior. Following this, the test results proved that all factors influence zakat behavior and there are partially various results. Among these factors are knowledge, belief, external motivation, work, and institutions; they have been shown to significantly influence zakat behavior. As for promotion, persuasion, internal motivation, WOM, income, distribution, and individual sales, the results proved that they have insignificant effect to the behavior of zakat people. Among these factors, personal income and sales showed a negative influence.